Determinants of Recent HIV Self-Testing Uptake Among Men Who Have Sex With Men in Jiangsu Province, China: An Online Cross-Sectional Survey - Li, Jianjun; Marley, Gifty; Zhang, Ye; Chen, Yunting; Tang, Weiming; Rongbin, Yu; Fu, Gengfeng (Frontiers in Public Health, 2021)
Background: To help inform regarding HIV self-testing (HIVST) upscale, we assessed the determinants of recent HIVST uptake among men who have sex with men (MSM) in Jiangsu province, China. Methods: We conducted a convenience online survey from March to April, 2020 among men aged ≥16 years, who had ever had sex with other men. Statistical analysis included Pearson's chi-square test, bivariate correlation, and multivariable logistic regression. p < 0.05 was considered statistically significant. Results: Of the total 692 participants, 69.5% (481) were aged between 18 and 40 years, and 65.9% (456) had reportedly ever self-tested. Using HIVST for first HIV test (aOR = 1.98, 95% CI: 1.21–3.26), perceiving HIVST as more private (aOR = 1.41, 95% CI: 0.85–2.35), and users not needing to go to a health facility (aOR = 1.68, 95% CI: 1.20–2.34) were associated with recent HIVST as facilitating factors. Conclusion: HIVST uptake rate has increased among Jiangsu MSM and can be further promoted by healthcare workers routinely recommending HIVST to their clients.